2016
DOI: 10.1002/tcr.201600069
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in the Chiral Brønsted Acid‐catalyzed Allylboration Reaction with Polyfunctionalized Substrates

Abstract: Asymmetric allylboration has played a central role in organic synthesis ever since the pioneering work by Hoffman and Brown, having found applications in the total synthesis of many natural products. A new dawn for this 40 year-old reaction occurred with the beginning of the new century when the first catalytic asymmetric methods came into play. In less than one decade, several methodologies, able to achieve the desired homoallylic alcohols with ee ranges in the high 90s, were developed. Among them, in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 82 publications
0
6
0
1
Order By: Relevance
“…Axially chiral phosphoric acids have shown to be effective in activating allyl, allenyl, and propargyl boronates in their reactions with aldehydes . Indeed, commercially available TRIP (Table ) exhibited asymmetric induction in the allyl transfer and the best reactivity profile among all examined catalysts (see Supporting Information for reaction optimization).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Axially chiral phosphoric acids have shown to be effective in activating allyl, allenyl, and propargyl boronates in their reactions with aldehydes . Indeed, commercially available TRIP (Table ) exhibited asymmetric induction in the allyl transfer and the best reactivity profile among all examined catalysts (see Supporting Information for reaction optimization).…”
Section: Methodsmentioning
confidence: 99%
“…After oxidative deboronation, 1,5-diol 2j was formed in 71 %yield and with ad.r. [20][21][22][23][24][25] Indeed, commercially available TRIP (Table 1) exhibited asymmetric induction in the allyl Scheme 2. We observed that addition of Sc(OTf) 3 or In(OTf) 3 led to decomposition of 1, while trifluoroacetic acid and AlCl 3 were viable catalysts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These data may represent matched/mismatched diastereoselectivity, wherein the influence of the ( S ) catalyst is matched to directing effects from the substrates, and the opposite bias of the ( R ) catalyst is mismatched and dominated by substrate factors . Taken together these observations suggest that these TRIP catalysts may be more effective when the intrinsic selectivity of the substrates is low and illustrate the challenges in applying stereochemical trends for relatively simple, achiral substrates to highly substituted, chiral variants, particularly polyhydroxylated frameworks with multiple, potentially ligating sites. , …”
mentioning
confidence: 88%
“…75a The exact geometry of the catalyst in the stereoinduction step has been investigated computationally by the Houk group 77 and the groups of Goodman and Pellegrinet. 78 The utility of this reaction has been thoroughly explored by the Fustero group 79 toward more complex products, including (1) relay allylation− RCM reactions for the synthesis of cyclic benzo-fused homoallylic alcohols; 80 (2) utilization of E-γ-silyl-allylBpin reagents for the synthesis of chiral allylic silanes; 81 and (3) use of aldehydes bearing tethered alkynes providing chiral ene-yne products, primed for various transition-metal-catalyzed cyclization reactions. 82 Another important advance within this realm is that of formal α-allylation reactions pioneered by the Kobayashi group.…”
mentioning
confidence: 99%